Overexpression of GDF15 protects kidneys from ischemia reperfusion injury and affects circular RNA expression - Cuilin Zhu; Cuilin Zhu; Qing Liu; Yale Su; Yale Su; Yixin Zhang; Yixin Zhang; Aanal Patel; Adam Greasley; Jifu Jiang; Douglas Quan; Douglas Quan; et al. (Frontiers in Cell and Developmental Biology, 2025)
BackgroundRenal failure and dysfunction remain one of the most significant morbidities impacting patient’s life. Effective treatments still lack in the context of an increasing number of patients with renal failure. This study aims to investigate the impact of growth differentiation factor 15 (GDF15) in treating renal dysfunction and to explore its therapeutic potential.MethodsRenal injury was induced with a murine ischemia reperfusion injury (IRI) model. Mice overexpressing GDF15 (GDF15 transgenic (GDF15TG) mice, GDF15 knock out (GDF15 KO) mice and wild type (WT) mice all underwent IRI to test the effects of GDF15 on renal injury. Renal function and histopathological changes were measured 24 h after reperfusion. Cell apoptosis was detected by TUNEL and tissue inflammation was detected by myeloperoxidase (MPO) activity. qRT-PCR was conducted to determine the expression of genes and circular RNAs.ResultsOverexpression of GDF15 reduced mortality of mice with lethal renal IRI whereas GDF15 deficiency increased the mortality. GDF15TG mice had better renal function with the lower levels of blood creatinine and blood urea nitrogen (BUN). Over-expression of GDF15 reduced kidney pathological changes, cell apoptosis, neutrophil infiltration and mortality. Over-expression of GDF15 also decreased the expression of apoptotic genes (high mobility group 1, HMGA1 and Bax), inflammatory genes IL-1β, IL-6, tumor necrosis factor (TNF-α), chemokine 1 (CK1), and senescent gene p21 whereas increases Bcl-XL, Importin 11 and CRIM1. IRI upregulated circular RNA Smad3 and reduced circular RNA Hipk3 and circular RNA Crim1, which was offset by GDF15.ConclusionOver-expression of GDF15 protects renal function and prevents renal failure, highlighting its potential in treating renal failure.